2019
DOI: 10.1021/acs.joc.9b01466
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Chemoselective [4 + 1] Cycloaddition Reaction toward Diverse 4-Methyleneprolines

Abstract: An efficient synthesis of 4-methyleneproline derivatives has been developed through an Rh-catalyzed [4 + 1] cycloaddition strategy using 3-methyleneazetidines and diazo compounds. The reaction proceeds under very mild conditions with a high degree of chemoselectivity, and competing experiments revealed that it is the preferred reaction, dominant over the C−H insertion, O−H insertion, and olefin cyclopropanation reactions which are commonly observed in Rh carbene chemistry. This method can incorporate the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…FTIR were performed to investigate the surface structure of the Li metal after immersing in BIA (Figure 1b). As shown in Figure 1b, compared with the pristine Li film, some new peaks at 1108, 1196, and 1614 cm −1 , which correspond to the C−N, C−O, and CO stretching vibrations, respectively, 26,27 can be observed for the Li metal after immersing in BIA. Furthermore, XPS was applied to analyze the surface compositions of Li metal after BIA treatment.…”
Section: Resultsmentioning
confidence: 95%
“…FTIR were performed to investigate the surface structure of the Li metal after immersing in BIA (Figure 1b). As shown in Figure 1b, compared with the pristine Li film, some new peaks at 1108, 1196, and 1614 cm −1 , which correspond to the C−N, C−O, and CO stretching vibrations, respectively, 26,27 can be observed for the Li metal after immersing in BIA. Furthermore, XPS was applied to analyze the surface compositions of Li metal after BIA treatment.…”
Section: Resultsmentioning
confidence: 95%
“…The pioneering works of multiple research groups have demonstrated the application of this approach for achieving 4-to 5-membered ring expansions through reacting with an azetidine with a diazo compound, leading to the formation of the corresponding pyrrolidine product (Figure 1A, left). [15][16][17][18][19] Considering the widespread usage of nitrogen heterocycles in various sectors of the chemical industry, particularly in the pharmaceutical field, the extension of this concept to other saturated N-heterocycles would be of immense value.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of skeletal editing of saturated N ‐heterocycles via one‐carbon insertion, one potential mechanism for achieving ring expansion involves the sequential formation of an ammonium ylide and subsequent [1,2]‐stevens rearrangement, enabling efficient one‐carbon ring expansion. The pioneering works of multiple research groups have demonstrated the application of this approach for achieving 4‐ to 5‐membered ring expansions through reacting with an azetidine with a diazo compound, leading to the formation of the corresponding pyrrolidine product (Figure 1A, left) [15–19] . Considering the widespread usage of nitrogen heterocycles in various sectors of the chemical industry, particularly in the pharmaceutical field, the extension of this concept to other saturated N ‐heterocycles would be of immense value.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering works of multiple research groups have demonstrated the application of this approach for achieving 4-to 5-membered ring expansions through reacting with an azetidine with a diazo compound, leading to the formation of the corresponding pyrrolidine product (Figure 1A, left). [15][16][17][18][19] Considering the widespread usage of nitrogen heterocycles in various sectors of the chemical industry, particularly in the pharmaceutical field, the extension of this concept to other saturated N-heterocycles would be of immense value.…”
Section: Introductionmentioning
confidence: 99%